Study of the keeping quality of cheese dip stored in PET Bottles: Sensory, physico-chemical, textural and microbiological aspects - Bansal, Venus; Kanawjia, uresh Kumar; Khetra, Yogesh; Debnath, Anindita (Indian Journal of Dairy Science, 2021)
This study aimed to evaluate the storage stability of novel cheese dip (CD) and cheese dip with spices (SCD) stored in PET bottles at refrigeration temperature (4Â±1Â°C). The change in quality attributes in terms of sensory, chemico-physical (pH, acidity, thiobarbituric acid (TBA), acid degree value (ADV) and color (L*, a*, b*)), textural and microbiological (total plate count, coliform and yeast and mold) were studied at an interval of 10 days. Also, linear regression models were developed to correlate the changes in attributes with storage time. Keeping quality of both CD and SCD decreased over the period of time. An increase in firmness, SPC, YM, TBA and ADV was observed for both the samples, whereas, pH, adhesiveness and sensory scores decreased. On day 30, SCD exhibited significantly lower acidity, ADV, TBA, tyrosine and microbial count than CD. Also, the sensory scores of SCD were significantly higher compared to CD. Linear regression equations between days and quality attributes showed determination coefficient (R2) >0.85. This study clearly shows that keeping quality of cheese dip depends on the composition and ingredients used fort its manufacturing. In conclusion, the spoilage of CD is mainly accompanied by increase in acidity owing to the growth of microorganisms which is responsible for decreased sensory scores and change in textural properties of the product. Accordingly, the heating time temperature combination can be altered to further improve the keeping quality of the product at refrigeration temperature.